Kowaiya : skeleton waltz chapter / cerita, Ahmad Mahdi; gambar oleh, Mustafa Kamal; penyunting, Toha Nasr - Ahmad Mahdi ; Mustafa Kamal ; Toha Nasr (Muffin Graphics, 2017)
158 halaman : ilustrasi ; 19 cm